Detection of bovine and porcine gelatine in dental materials - Nining Irfanita binti Irfan (International Institute for Halal Research and Training, International Islamic University Malaysia, 2019)
The rapid innovation of technology leads to the availability of a variety of products, including medical and dental products which may contain ingredients that are from prohibited sources. The presence of pig derivatives, such as porcine gelatine, in any products is prohibited to be consumed by Muslim. The presence of gelatine is not limited to food products but has also been found in medical and dental products. Most dental materials available in Malaysia are imported from other countries and might contain gelatine which is a protein derived either from porcine, bovine or other animal sources. Authentication of gelatine is crucial due to religious and health concerns. Therefore, this study aimed to detect porcine and bovine gelatine in dental materials using attenuated total reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR) combined with Principal Component Analysis (PCA) and Polymerase Chain Reaction (PCR). Forty-two dental material samples were analyzed in this study. ATR-FTIR analysis was carried out in order to distinguish the spectra between gelatine bovine and porcine gelatine standards. These spectra were then compared to the spectra of the dental material samples. All acquired data from ATR-FTIR were subjected to data pre-processing followed by PCA. Detection and discrimination of gelatine standards (bovine and porcine) and gelatine in dental materials were successfully achieved using ATR-FTIR combined with PCA within a small region, which is between wavenumber 1756-1584 cm-1 (Amide Ⅰ and Amide II). Detection and discrimination of porcine and bovine gelatine were also carried out using conventional PCR. PCR methods were run to verify the presence of porcine and bovine in dental materials. Species-specific primers targeting the 212 bp porcine Cytochrome b gene and 271 bp bovine Cytochrome b were used to amplify both DNA in nine dental material samples. The species-specific primers were found to be specific and sensitive. The detection limit of DNA concentration was 0.001 ng/μL and 0.0001 ng/μL for bovine and porcine gelatines, respectively. Using PCR, one sample, BDM 01 was found to contain porcine DNA while two samples (BDM 01 and BDM 14) were found to be positive for bovine DNA. The presence of porcine DNA was also evaluated using commercial Mericon pig kit. However, the pig kit did not detect the presence of porcine DNA in all dental material samples. The findings suggested that ATR-FTIR combined with PCA and conventional PCR are applicable in the identification of porcine and bovine gelatine in highly processed products such as dental materials.